Prevention of traumatic injuries and dental treatment of epileptic patients - Gawlak, Dominika; Mańka-Malara, Katarzyna; Łuniewska , Joanna; Hovhannisyan, Anahit; Stojak, Wiktoria; Stróżyńska, Anna; Kamiński, Tomasz (Journal of Stomatology, 2015)
Epileptic patients constitute a group with specific dental care needs. The necessity to prevent traumatic injuries to the head and oral cavity is emphasized in literature as these occur in this group considerably more often than in other patients. In consequence, the use of custom-made mouthguards is specifically promoted in this group since their shock dissipation ability effectively protects soft and hard oral tissuesagainst injuries during epileptic seizures.